Elaboración de un prototipo de sistema controlador de carga de baterías de ácido plomo e ion litio de 24v por medio de energía solar - Salomón-Aguilar, Mauricio (Instituto Tecnológico de Costa Rica, 2017)
This document allows to collect in detail the process of design and implementation of a prototype solar charger system of 24V batteries of lead acid and lithium ion at the Technological Institute of Costa Rica. This project is part of the research projects of the laboratorio de sistemas electrónicos para la sostenibilidad (SESlab). The importance of this project is to encourage the use of alternative transportation such as electric bicycles, both University staff and students of the Instituto Tecnológico de Costa Rica central Campus, due to the large number of vehicles that enter daily to the central Campus. The research process focused on the use of photovoltaic energy to charge lead-acid and lithiumion batteries of 24V. For the design of the prototype, it is necessary a system that performs an adequate processing of energy received from a photovoltaic module, so that it uses this energy to charge the batteries, as well as a system of monitoring and control that allows the proper process of charge of battery, as well the extraction of maximum power of the photovoltaic module when this is necessary.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2017.
Keywords: Caracterización; Energía renovable; Estado de carga; Irradiancia; MPPT; RTC